MEASUREMENT OF PUBLIC SERVICE PERFORMANCE THROUGH COMMUNITY SATISFACTIONINDEX(IKM) TO PUBLIC SERVICE QUALITY ON EIGHT DISTRICTS OFFICE AT SOUTH BANGKA REGENCY YEAR 2014 - Darus Altin (Universitas Teuku Umar, 2018)
Abstract: Sub-District government as one of the unitslocal government organization has a strategic position being at the forefront of dealing directly with community needs many different background and demand of the ever changing and envolving.Therefore South Bangka Regency Government began to improve immediately public service especially in the areas of health, education and licensing which is seen as something that relates direcly to the public. Form of this is to measure of community satisfaction index.The purpose of this study is excepted to be taken info consideration to establish a policy with the goal of increasing the service element that quality still needs improvement and drivers of each unit of service providers to increase service quality especially public service unit at South Bangka Regency. The result of community satisfasction index survey on the implementation of public service through community satisfaction index on Eigth Districts at South Bangka Regency year 2014 overall reach 72.22 or categories of service quality in the category “B” or service performance “GOOD”.Value of Community satisfaction index the highest achieved by Districs Toboali with achievement 77.92 and service quality “B” (good performance), and the IKM lowest value obtained by Simpang Rimba Districts with IKM Value 66.35.3 Units of the Service from 8 districts at South Bangka Regency has IKM Value above the average IKM value that is: Districts Toboali, Districts Kepulauan Pongok, dan Districts Air Gegas.There are stil some units of service needs to be improved, so it is recommended their advanced studiesor surveys on each unit of service to determine the problem lies deeper.Generally the ideal condition excepted by the public is improving the quality of service bureaucracy by creating procedures and working mechanism that is easy, simply, brief, facilitate the service requirements that are not directly speed up service time, the certainty of schedule, improving the ability of service personal and repair clarity, discipline, as well as the presence of service personnel in place.People also expect the change to the element of convenience in the form of environmental service office, parking facilities, suggestion boxes, complaint means, a lounge area, as well as concerning the equipment, and facilities infrastructure for public services.Keywords: Public Service, South Bangka Regency, Community Satisfaction Index (IKM), Kep/25/M.Pan/2/2004,